2021
DOI: 10.34067/kid.0002172021
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for SARS-CoV-2 Spike Protein in the Urine of COVID-19 Patients

Abstract: Background: SARS-CoV-2 infection has so far affected over 133 million people worldwide, causing over 2.5 million deaths. With the large majority of SARS-CoV-2 infected individuals being asymptomatic, major concerns have been raised about possible long-term consequences of the infection. Methods: We developed an antigen capture assay to detect SARS-CoV-2 spike protein in urine samples from COVID-19 patients whose diagnosis was confirmed by PCR from nasopharyngeal swabs (NP-PCR+). The study used a collection of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 38 publications
3
30
0
Order By: Relevance
“…Establishing the kinetics of S protein in vivo may provide valuable diagnostic and therapeutic insights. The presence of S protein in patients’ blood was previously reported by another group [ 52 ]. In our study, low amounts of the S protein could be detected in pre-pandemic control sera.…”
Section: Discussionmentioning
confidence: 52%
“…Establishing the kinetics of S protein in vivo may provide valuable diagnostic and therapeutic insights. The presence of S protein in patients’ blood was previously reported by another group [ 52 ]. In our study, low amounts of the S protein could be detected in pre-pandemic control sera.…”
Section: Discussionmentioning
confidence: 52%
“…The importance of ACE2 expression in syncytia formation is underscored by the fact that syncytia formation also occurred in Vero E6 cells (which express ACE2), when Vero E6 cells are transfected with spike plasmid; in contrast, HEK293 cells, which do not express ACE2 protein, do not form syncytia when transfected with spike plasmid. The clinical relevance of the current approach in investigating spike protein-dependent kidney disease in COVID-19 is thus validated because of the following salient findings in the recent literature: first, cell spike protein expression per se causes cell adherence to neighboring ACE2-expressing cells [24] ; second, SARS-CoV-2 is present in the urine of patients with COVID-19, and the viral titer correlates with AKI and mortality [17] ; third, the spike protein is present in urine in patients with COVID-19 and AKI [18] .…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, the SARS-CoV-2 virus is detected in the urine in patients with COVID-19; the virus co-localizes with the ACE2 receptor in tubular epithelial cells as demonstrable on renal biopsy; and higher viral titers in the urine correlate with AKI and increased mortality [17] . Moreover, in over 25% of humans with COVID-19 and AKI, the spike protein is present in urine [17] , [18] . How the spike protein reaches the urinary space is uncertain, but on a priori grounds, this may reflect filtration of the SARS-CoV-2 virus/its spike protein from plasma across the glomerular filtration barrier; the sloughing of spike protein into the urinary space from the plasma membrane of kidney cells infected with SARS-CoV-2; or the sloughing of kidney cells infected with the virus into the urinary space and the subsequent detachment of the spike protein from cell membranes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study has shown that the spike protein of SARS-CoV-2, particularly subunit S1, can be detected in the urine of patients with a nasopharyngeal RT-qPCR-positive result using an antigen-capture assay. However, sensitivity of this methodology is highly reduced compared to nasopharyngeal RT-qPCR (only 25% of SARS-CoV-2 infected individuals are detected) [ 20 ].…”
Section: Introductionmentioning
confidence: 99%